Educational inequality in consumption of in natura or minimally processed foods and ultra-processed foods: The intersection between sex and race/skin color in Brazil - Crepaldi, Barbara Virginia Caixeta; Okada, Letícia Martins; Claro, Rafael Moreira; Louzada, Maria Laura da Costa; Rezende, Leandro F. M.; Levy, Renata Bertazzi; Azeredo, Catarina Machado (Frontiers in Nutrition, 2022)
Background: It remains uncertain how the intersection between educational, gender, and race/skin color inequalities influences food consumption in Brazil. In this study, we examined the educational inequality in the consumption of in natura/minimally processed and ultra-processed foods by Brazilians with an intersectional perspective between sex and race/color. Methods: We used cross-sectional data from the Telephone Surveillance System (VIGITEL 2019), comprising 52,443 participants ≥18 years. Daily food consumption was considered high when consumption of ≥5 foods for each food group was reported the day before the survey. Educational inequality in food consumption was assessed by the slope index of inequality (SII) and the relative index of inequality (RII) according to sex and race/color (White; Black/Brown). Positive SII and RII values >1.0 indicate higher food consumption among more educated participants. Results: The consumptions of in natura/minimally processed and ultra-processed foods were more prevalent in those with the highest level of education (≥12 years) and intermediate education (9-11 years), respectively. However, highly educated white women had higher consumption of in natura/minimally processed foods than black women with the same education level, and white men in low and intermediate school levels had higher consumption of these foods than black men with the same education levels. We found higher absolute educational inequality for in natura/minimally processed foods among White women (SII 21.8, 95% CI 15.3, 28.4) and Black/Brown men (SII 19.3, 95% CI 12.5, 26.1). Black/Brown men (SII 7.3, 95% CI 0.5, 14.0) and Black/Brown women (SII 5.6, 95% CI 1.0, 10.2) had higher absolute educational inequality than White men (SII -3.3, 95% CI -10.9, 4.3; P=0.04) in the consumption of ultra-processed foods. Conclusions: Educational inequalities influenced the consumption of in natura/minimally processed more than ultra-processed foods, and, for the latter, inequalities were greater among Black/Brown men and women than among White men.